PENGARUH PENYULUHAN KESEHATAN TERHADAP PENGETAHUAN DAN PERILAKU SADARI PADA REMAJA PUTRI DALAM UPAYA PENCEGAHAN CA MAMMAE DI SMA NEGERI 6 PEKANBARU - Yulianti Anhar; Melly Melly; Masnun Masnun (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2020)
Ca mammae is a disease caused by excessive growth of cells in the breast. Ca Mammae is the biggest case in Indonesia because the patients can experience death. The risk of Ca Mammae can caused by the lack of knowledge in teenagers. The knowledge is obtained from health educations with changing recipients behaviour purpose. SADARI is needed for teenagers to prevent the occurrence of Ca Mammae. The purpose of this research is to determine the effect of health education towards the awareness of teenage girls in the effort of preventing Ca Mammae in State High School 6 Pekanbaru. Quantitative research type is used with Pre Experimental research method with One Group Pretest-Posttest Design design with the sample of 60 students. The instrument used is questionnaires. Data Analysis uses Wilcoxon Test. P values obtained from the research result of SADARI knowledge and from SADARI behaviour is 0.000, indicates that p value < α (0.05), so there is an effect of health education to increase in knowledge and SADARI behaviour of the teenage girls in order to prevent Ca Mammae. Therefore, SADARI health education in educational institution is needed to increase the knowledge and able to form a healthy behaviour for teenagers.